Duration of plasma oxytetracycline levels in neonatal pigs - D Schoneweis; S Hummels; L Schulteis (Kansas Agricultural Experiment Station Research Reports, 1981)
Samples from neonatal pigs were evaluated to determine the persistence of plasma oxytetracycline after injecting LA 200Â®. Significant (minimum of .2 mcg/ml) amounts of oxytetracycline were found in all samples 96 hours after the injection, and oxytetracycline still persisted in many pigs after 168 hours.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Plasma oxytetracycline; Neonatal pigs